Ambient Media Advertising - A New Era of Creativity - Tanwar, Shweta (Indian Journal of Marketing, 2007)
The field of marketing communication is very dynamic. It keeps on evolving. As a result of this it is a highly demanding area. Every time there a thirst for something new which can attract the audiences and satisfy their hunger for something new and innovative and at the same time it must be cost effective. In this regard advertisers have coined a new way of advertising and it is some what a revolution in the field of advertising. It is "Ambient Advertising" highly creative and highly unusual both in its message and location where it appears. This paper deals with ambient advertising. Its meaning, characteristics and how it is doing in India.